Understanding osteosarcomas. Issue 8 (August 2018) - Simpson, Emily; Brown, Heather L.
Abstract : ABSTRACT: This article reviews the cause, clinical presentation, diagnostic methods, and management of osteosarcoma, the most common primary bone tumor and third most common cancer among children and adolescents. In the 1970s, the introduction of adjuvant chemotherapy following tumor resection improved overall 10-year survival from 30% to about 50% of patients. However, since that change in management strategy, the survival rate has since plateaued, with no improvement in overall 10-year survival since the 1990s. A better understanding of this disease is the first step to help improve these numbers.